Judicial Wellness Initiative: A Conceptual Framework for Supporting the Sustainable System of Modern Judiciary - Ramadhan , Solihin Niar (Judex Laguens, 2023)
The Covid-19 pandemic has given us a valuable lesson that the most important asset of the judiciary besides its infrastructure, is the soundness of judges. Several factors such as ongoing family problems, high demand for judicial and non-judicial tasks, strict surveillance activities, and high public expectations of the court’s performance increasingly affect judges’ health extent. The amount of physical and psychological pressure experienced by judges in carrying out their duties directly impacts the court’s performance and the quality of delivered judicial services. To support the implementation of the modern judicial system, the judge's physical and psychological soundness must be considered carefully. Unfortunately, the wellness protection of judges in Indonesia is still hitherto not a distinctive concern. Through a Business Ecosystem approach, the Judicial Wellness Initiative is formulated as an alternative solution that can be implemented as a synergy between IKAHI and other related parties for supporting the fulfilment of the judges’ well-being. The Judicial Wellness Initiative scheme is hopefully expected to assist judges who are experiencing physical and mental health matters. Addressing the judges’ health problems directly affects the quality of the court’s performance and therefore, a sustainable modern judicial system can be realized.